Research on the Influence of Metamaterials on Single Photon LiDAR - Hu, Yingying; Xu, Duoduo; Zhou, Zehui; Zhao, Tianqi; Shi, Yan; Tian, Ying; Xu, Rui; Chen, Yi (Frontiers in Physics, 2020)
Single photon light deteation and ranging (LiDAR) has the advantages of high angle and distance resolution, great concealment, strong anti-active jamming capability, small volume, and light mass, and has been widely applied in marine reconnaissance, obstacle avoidance, chemical warfare agent detection, and navigation. With the rapid development of metamaterial, the performance of single photon LiDAR system would be improved by optimizing the core devices in the system. In the paper, we first analyzed the performances index of single photon LiDAR and discover the potential of metamaterial in improving the system performance. Then, the influence of metamaterials on the core devices of single photon LiDAR was discussed, including laser, scanning device, optical lens and single photon detector. As a result, we get the conclusion that through effective light field modulation, the metamaterials technology might push the performance innovation of single photon LiDAR.